Psychological well-being and coping strategies among secondary school teachers: A cross-sectional study - Chinthana Rajesh; Lena Ashok; Chythra R Rao; Veena G Kamath; Asha Kamath; Varalakshmi Chandra Sekaran; Virupaksha Devaramane; V Thippe Swamy (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: Educators, academicians, and teachers are responsible for the development of the nation's human capital. Teacher coping methods are becoming more widely recognized as a key factor in determining teacher effectiveness. The aim of this study was to identify the various coping strategies adopted by high school teachers in Southern India. MATERIALS AND METHODS: A cross-sectional study was conducted in government, aided, and unaided schools of Udupi, a coastal district in Southern India. A self-administered questionnaire was used to collect the data from 460 high school teachers chosen based on convenience sampling. The coping strategies were identified using a modified version of Brief COPE(Coping Orientation to Problems Experienced) Inventory (Carver, 1997). Data were entered using SPSS version 15 and descriptive statistics was performed. RESULTS: The study found that teachers had moderate level of coping skills in all domains. The most popular coping techniques used by secondary school teachers were positive reframing, active coping, and planning; nevertheless, substance use was recognized as the least popular coping strategy. CONCLUSION: Positive reframing, active coping, and preparation were the most commonly used coping strategies by the teachers in the survey. Teachers are a vital resource who have received less attention than they deserve for their psychological well-being. A customized intervention program based on their perceived needs could be a good place to start.